Assessing the Online Scientific Community’s Support for Various Reasons for Article Retraction: A Preliminary Survey - Namuth, August; Brown, Mitch; Macchione, Alicia; Sacco, Donald (ETHICS IN PROGRESS, 2023)
A prevailing lay understanding of retraction in the scientific literature is to correct for misconduct and honest errors. Nonetheless, though historically rare, retractions to limit the spread of results deemed socially harmful (i.e., information hazards), have gained increasing traction and become increasingly common. This study sought primarily to determine the extent to which information hazard-based retraction is supported in the scientific community and as a secondary goal whether individual difference variables moderate receptivity. We tasked a diverse sample of researchers across various disciplines who use social media to evaluate scenarios in which a paper was retracted for misconduct, honest errors, and information hazards. Overall, support for retraction on the basis of information hazards was low, suggesting that researchers overwhelmingly support academic freedom as a concept. Nonetheless, left-leaning ideologies predicted slightly greater defensibility of the practice among individuals early in their careers. We provide training suggestions to mitigate reactance toward controversial scientific findings.